Expression and replication studies to identify new candidate genes involved in normal hearing function. - Girotto, Giorgia; Vuckovic, Dragana; Buniello, Annalisa; Lorente-Cánovas, Beatriz; Lewis, Morag; Gasparini, Paolo; Steel, Karen P (PLoS One, 2014)
Considerable progress has been made in identifying deafness genes, but still little is known about the genetic basis of normal variation in hearing function. We recently carried out a Genome Wide Association Study (GWAS) of quantitative hearing traits in southern European populations and found several SNPs with suggestive but none with significant association. In the current study, we followed up these SNPs to investigate which of them might show a genuine association with auditory function using alternative approaches. Firstly, we generated a shortlist of 19 genes from the published GWAS results. Secondly, we carried out immunocytochemistry to examine expression of these 19 genes in the mouse inner ear. Twelve of them showed distinctive cochlear expression patterns. Four showed expression restricted to sensory hair cells (Csmd1, Arsg, Slc16a6 and Gabrg3), one only in marginal cells of the stria vascularis (Dclk1) while the others (Ptprd, Grm8, GlyBP, Evi5, Rimbp2, Ank2, Cdh13) in multiple cochlear cell types. In the third step, we tested these 12 genes for replication of association in an independent set of samples from the Caucasus and Central Asia. Nine out of them showed nominally significant association (p<0.05). In particular, 4 were replicated at the same SNP and with the same effect direction while the remaining 5 showed a significant association in a gene-based test. Finally, to look for genotype-phenotype relationship, the audiometric profiles of the three genotypes of the most strongly associated gene variants were analyzed. Seven out of the 9 replicated genes (CDH13, GRM8, ANK2, SLC16A6, ARSG, RIMBP2 and DCLK1) showed an audiometric pattern with differences between different genotypes further supporting their role in hearing function. These data demonstrate the usefulness of this multistep approach in providing new insights into the molecular basis of hearing and may suggest new targets for treatment and prevention of hearing impairment.
Keywords: Adult; Animals; DNA Replication; Gene Expression Profiling; Genome-Wide Association Study; Genotype; Hair Cells, Auditory; Hearing; Humans; Mice; Phenotype; Polymorphism, Single Nucleotide; Stria Vascularis

Evidence of inbreeding depression on human height. - McQuillan, Ruth; Eklund, Niina; Pirastu, Nicola; Kuningas, Maris; McEvoy, Brian P; Esko, Tõnu; Corre, Tanguy; Davies, Gail; Kaakinen, Marika; Lyytikäinen, Leo-Pekka; Kristiansson, Kati; Havulinna, Aki S; et al. (PLoS Genet, 2012)
Stature is a classical and highly heritable complex trait, with 80%-90% of variation explained by genetic factors. In recent years, genome-wide association studies (GWAS) have successfully identified many common additive variants influencing human height; however, little attention has been given to the potential role of recessive genetic effects. Here, we investigated genome-wide recessive effects by an analysis of inbreeding depression on adult height in over 35,000 people from 21 different population samples. We found a highly significant inverse association between height and genome-wide homozygosity, equivalent to a height reduction of up to 3 cm in the offspring of first cousins compared with the offspring of unrelated individuals, an effect which remained after controlling for the effects of socio-economic status, an important confounder (χ(2) = 83.89, df = 1; p = 5.2 × 10(-20)). There was, however, a high degree of heterogeneity among populations: whereas the direction of the effect was consistent across most population samples, the effect size differed significantly among populations. It is likely that this reflects true biological heterogeneity: whether or not an effect can be observed will depend on both the variance in homozygosity in the population and the chance inheritance of individual recessive genotypes. These results predict that multiple, rare, recessive variants influence human height. Although this exploratory work focuses on height alone, the methodology developed is generally applicable to heritable quantitative traits (QT), paving the way for an investigation into inbreeding effects, and therefore genetic architecture, on a range of QT of biomedical importance.
Keywords: Adult; Aged; Body Height; Consanguinity; Databases, Genetic; Family; Female; Genes, Recessive; Genetic Heterogeneity; Genome-Wide Association Study; Homozygote; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable